IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE THROUGH COLLABORATIVE WRITING STRATEGY - Emilda Ramadona; Iskandar Zulkarnain; Meida Rabia Sihite (English Education Study Program FKIP Universitas Alwashliyah Medan, 2021)
The objective of this research is to improve students’ achievement in writing descriptive through collaborative writing. This research was conducted at SMP Negeri 28 Medan academic year 2018-2019 as the subject of researcher. The subject of this research consisted of 35 students of the eighth grade. The research was conducted with classroom action research. The research was conducted by dividing into two cycles with 6 meeting for each. The sources of data were qualitative and quantitative. The qualitative data were collected by observation sheets, questionnaires and diary notes. Quantitative data were taken from tests, carried out at the end of every cycle. Based on the result of the data analysis there was an improvement of the result of the students’ achievement in writing descriptive text from each cycle. After doing test on cycle I, there was an improvement of the result of the students’ mean was 72.8 with 24 students who got successful score criteria above 70 or it was 69 % and 11 students who got unsuccessful score criteria above 70 or it was 31 %. Then, an improvement was done in second cycle after reflection in the first cycle, there was an improvement of students’ mean was 77.9 with 31 students who got successful score criteria above 70 or it was 89 % and 4 students who got unsuccessful score criteria above 70 or it was 11 %. In other words, the students’ achievement at writing descriptive text was improved. And based on questionnaire sheets, observation sheets, diary notes, and documentation, it showed that the expression and excitement of the students were also improved.